The Effect of Capital Structure, MVA, and Dividend Yield on Stock Prices in the Industrials Sector on the IDX in 2021–2024 - Hasmi Wirianti; Nur Anita (Majapahit Journal of Islamic Finance and Management, 2025)
Fluctuations in stock prices in the Industrials sector on the Indonesia Stock Exchange show that investors consider fundamental factors in decision-making. However, the results of previous research related to the influence of capital structure, company value, and dividend policy are still inconsistent, so a new study is needed. This study aims to analyze the influence of capital structure (DER), Market Value Added (MVA), and dividend yield on stock prices. The research uses a quantitative method with multiple linear regression based on secondary data from the IDX's financial statements and share prices. The sample consisted of 9 companies with 36 observations. The results of the classical assumption test showed that the model met the requirements of normality, multicollinearity, heteroscedasticity, and autocorrelation did not occur. Partial tests showed that DER (Sig = 0.075) and MVA (Sig = 0.058) had no significant effect, while dividend yield had a significant negative effect (Sig = 0.003). Simultaneous tests showed a significant influence of the three variables with a Calculation of 4.502 and a Sig of 0.010. The Adjusted R² of 0.231 shows that other variables are more dominant in influencing the stock price. Further research is suggested to add variables and extend the analysis period.